Is Environmentalism the Right Strategy to Decarbonize the World? - Marco A. Marini; Ornella Tarola; Jacques-François Thisse (Fondazione Eni Enrico Mattei (FEEM), 2020)
We study how the supply of environmentalism, which is defined by psychic benefits (costs) associated with the purchase of high-environmental (low-environmental) qualities, aects the way firms choose their products and the ensuing consequences for the global level of pollution. Contrary to general belief, a high supply of environmentalism does not give rise to a better environmental outcome because it endows firms with more market power which they use to maximize profits. By contrast, standard policy instruments such as a minimum quality standard or the use of greener technologies leads to a better ecological footprint.
Keywords: D11; L13; Q50; 330; Environmentalism; Psychic Costs and Benefifits; Vertical Product Differentiation; Environmental Policy